Phytoseiid mites (Acari: Mesostigmata: Phytoseiidae) in Nanling National Nature Reserve, Guangdong, China - Fang, Xiao-Duan; Ouyang, Ge-Cheng; Wu, Wei-Nan (Zootaxa, 2020)
Nanling National Nature Reserve is the biggest natural reserve in Guangdong Province. It is located on the south side of the Nanling middle mountain range, bordering on Hunan Province. During Oct. 28–Nov. 2, 2018, a survey was carried out to investigate the fauna of phytoseiid mites in Nanling National Nature Reserve. A total of 17 species in eight genera and two subfamilies was recorded, including two new species Transeius conyzoides Fang & Wu sp. nov. and Typhlodromus (Anthoseius) huangjiaensis Fang & Wu sp. nov. A checklist of all species is presented in this paper, and the two new species are described and illustrated.